THE INFLUENCE OF LEADERSHIP EMPOWERING AND JOB STRESS ON PERFORMANCE WITH INNOVATION IN THE WORKPLACE AS AN INTERVENING VARIABLE - Gita Danu Pranata; Nurfajriyah Aulia Azhar (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
This research aims to determine the effect of empowering leadership and stress on performance with innovation in the workplace as an intervening variable. The sample technique for this research uses a non-probability sampling technique with a saturated sample method, where all members of the population are used as samples. The data collection technique used a questionnaire in the form of a Google form and collected 83 respondents. The method used to analyze the data in this research is path analysis with the SPSS version 22 program. The results of this research show that Empowering Leadership has a positive and significant effect on Innovation, Job Stress has a negative and significant effect on Innovation, Empowering Leadership has a positive and significant effect on Employee Performance , Work Stress does not have a significant effect on Employee Performance, Innovation has a positive and significant effect on Employee Performance, Innovation can mediate Empowering Leadership on Performance, Innovation cannot mediate Work Stress on Employee Performance.